SME Finance and Economic Development Paradox: The Case of Fish Industry in The Gambia - Jaabi, Seeku A K (Advances in Social Sciences Research Journal, 2018)
While the literature on enterprise finance focuses largely on manufacturing industry and in developing countries concerns enterprises in clustering industry, this study attempts to fill the gap by examining enterprise financing experiences in the fishing industry of The Gambia. Despite SMEs as spring board of industrialisation and development in most developing countries, they continue to face acute formal financial constraints. It is argued that the controversy in the empirical literature on the financing decisions on SMEs is based on the failure to take into account the degrees of information opacity, enterprises’ capabilities and needs at specific stages of their life cycles. Fish as an agricultural commodity is perishable requiring capabilities and institutional developments to maintain freshness, and quality standards to boost production, processing and exports to lucrative markets and these require considerable financing requirements. The study adopted a mix approach using qualitative questionnaire survey and quantitative approach to assess the source and challenges of fish SME financing. The findings revealed that fish enterprises’ access to formal financial credit is limited to supporting its production, processing and exports in The Gambia. The developmental role of government, innovative lending technologies of financial intermediaries and leasing firms can be instrumental in addressing the SMEs’ persistent financing difficulties to enhance overall socio-economic developments. This makes fish SME financing study unique and complex in enterprise financing literature.